3D Printing β-TCP-laden GelMA/Alginate interpenetrating-polymer-network biomaterial inks for bone tissue engineering - de Souza, Joyce R [UNESP]; Rahimnejad, Maedeh; Soares, Igor P Mendes [UNESP]; Anselmi, Caroline [UNESP]; de Oliveira, Pedro H C [UNESP]; Dos Reis-Prado, Alexandre H; Maglaras, Victoria; Dal-Fabbro, Renan; Trichês, Eliandra S; Bottino, Marco C (Elsevier, 2025)
Bone's capacity for self-repair is limited when large defects arise from trauma or infection. Traditional grafting methods like autografts and allografts often face challenges like immune rejection and limited availability. Traditional scaffold manufacturing techniques for bone tissue engineering frequently lack precise control over the constructs' material composition and pore architecture. Recently, 3D printing technology, particularly with interpenetrating polymer networks (IPNs), has successfully addressed these limitations, improving biocompatibility, strength, and degradation. Our study investigated gelatin methacryloyl (GelMA)/Alginate IPNs laden with beta tri-calcium phosphate (β-TCP) particles in a 3D-printed format to optimize cell proliferation and tissue regeneration conditions. Rheology studies showed shear-thinning viscosity and fast recovery (~90%) to primary viscosity after stress removal, confirming the inks' suitability for extrusion-based printing. Both inks demonstrated high resolution and acceptable printability (0.9-1). Incorporating β-TCP increased the compressive modulus (0.09±0.01 MPa for the control group vs. 0.15±0.01 MPa for 15% (w/v) β-TCP, ***p < 0.001) and swelling ratio, decreasing biodegradation over 35 days. Cell assays showed enhanced cell proliferation over 7 days, with no significant differences between groups. Compared to basal and osteogenic media controls, higher mineralization and osteogenic gene expression were observed in 15% β-TCP-laden 3D-printed constructs on days 14 and 21. Histological analysis in vivo showed no signs of inflammation after three weeks, suggesting favorable tissue compatibility. Furthermore, calcium carbonate deposits were identified, evidencing the successful differentiation of mesenchymal stem cells into cells capable of producing a mineralized matrix. This study demonstrated that the (GelMA)/Alginate IPN containing β-TCP could be a successful biomaterial ink with promising bioactive properties for bone tissue engineering.